3D in situ stress state modelling and fault reactivation risk exemplified in the Ruhr region (Germany). (December 2022) - Kruszewski, Michal; Montegrossi, Giordano; Balcewicz, Martin; de Los Angeles Gonzalez de Lucio, Gabriela; Igbokwe, Onyedika Anthony; Backers, Tobias; Saenger, Erik H.
Abstract: Throughout the 700-yearlong coal exploration period in the Ruhr region, an abundance of geological, geophysical, seismic, and in situ stress data was obtained from the Carboniferous strata. In this study, we take advantage of this unique dataset to develop a static 3D geomechanical model to predict the spatially continuous distribution of undisturbed in situ stress state and evaluate the reactivation risk of major fault zones. Compared to the point-wise stress information, the spatially continuous in situ stress state provides an effective tool for planning subsurface operations and assessing seismic hazards in areas where no stress information is available. The developed model was validated against a comprehensive calibration dataset including results from geophysical logging, borehole deformation, and fault-slip analysis, in situ hydrofracturing measurements, distribution of subsidence, microseismicity, and observations from coal mining activities. Consequently, interpretation and assessment of the model results including their uncertainties, reliability, limitations, and perspectives are discussed. The possible applications of the model approach for seismic hazard prediction and utilization of deep geothermal energy in the Ruhr region are outlined. Highlights: 3D in-situ stress state quantification using numerical modelling was presented. Developed numerical model was validated against a comprehensive calibration dataset. Spatially continuous stress state is an effective tool for subsurface operations. It is expected that NW-SE and NNW-SSE geological structures are critically stressed. SW model areas are the best suited for the exploration of geothermal resources.